Measurement of the Jet Size Dependence of Inclusive Jet Suppression in Lead-Lead Collisions at √sNN = 2.76 TeV with the ATLAS Detector - Aad, G. (2013)
Measurements of inclusive jet suppression in heavy ion collisions at the LHC provide direct sensitivity to the physics of jet quenching. In a sample of lead-lead collisions at √ sNN = 2.76 TeV corresponding to an integrated luminosity of approximately 7 µb −1 , ATLAS has measured jets with a calorimeter system over the pseudorapidity interval |η| < 2.1 and over the transverse momentum range 38 < pT < 210 GeV. Jets were reconstructed using the anti-kt algorithm with values for the distance parameter that determines the nominal jet radius of R = 0.2, 0.3, 0.4 and 0.5. The centrality dependence of the jet yield is characterized by the jet “central-to-peripheral ratio,” RCP. Jet production is found to be suppressed by approximately a factor of two in the 10% most central collisions relative to peripheral collisions. RCP varies smoothly with centrality as characterized by the number of participating nucleons. The observed suppression is only weakly dependent on transverse momentum. A significant dependence of the RCP on the jet radius is observed for jets with pT < 100 GeV. These results provide the first direct measurement of inclusive jet suppression in heavy ion collisions and complement previous measurements of dijet transverse energy imbalance at the LHC